The Role of Social Media in Promoting Tourism Villages: A Case Study in Semarang Regency - Yogi Bachtiar; Bambang Bernanthos (Journal of Social Research, 2024)
This research highlights the role of social media in promoting tourist villages in Semarang Regency, Central Java Province. With the advancement of information and communication technology, social media platforms such as Instagram and Facebook have become effective tools for increasing awareness and visitor traffic to tourist villages. Through various digital promotion strategies, tourism village managers can attract visitor interest with engaging and informative content. The results of the study indicate that the higher the intensity of social media use by tourists, the greater the likelihood of them visiting tourist villages. Additionally, age differences influence responses to digital promotions; younger generations tend to be more influenced by interactive and visual promotions, while older groups rely more on information from traditional sources. Despite the many advantages of social media, this study also identifies several limitations, such as a limited sample size and potential bias in the questionnaire. Furthermore, the rapid development of technology may affect the relevance of the results in the future. Nevertheless, overall, this research provides guidance for tourism village managers to leverage social media as a dynamic and adaptive promotional tool in response to changing digital trends.